The origins of New Zealand's first government house. (3rd May 2016) - Maxwell, Justin; Woods, Naomi; Robinson, James
Abstract : SUMMARY: In 1842 the former first government house located at Okiato, New Zealand, burnt to the ground and the site was abandoned. A well on the site was excavated in 1994–95, revealing a base layer of burnt timbers, a Maori digging stick and ceramic sherds with an estimated manufacture date range of 1823–41. We argue that this deposit is derived from the 1842 destruction of the Okiato government house building. An analysis of the wood identified kauri (Agathis australis ) and kahikatea (Dacrycarpus dacrydioides ), confirming that the building was not a prefabricated imported structure, but rather was constructed on site from locally available timber.